Berkeley en 90 minutos - Strathern, Paul, 1940-; Padilla Villate, José Antonio; Strathern, Paul, 1940- (Tres Cantos, Madrid, España : Siglo XXI de España Editores, S.A., 2015)
A brief and enlightening exploration of the philosopher's life and ideas is presented in an entertaining and accessible fashion.
Online resource; title from ePub title page (Digitalia, viewed June 28, 2017)
Keywords: Berkeley, George, -- 1685-1753.; Philosophers -- Biography; Electronic books